Perception, Attitude and Knowledge about Medico-Legal Post Mortem Examination: A Study on Para-Clinical Medical Students (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Medico-Legal Post-Mortem Examination (MLPME) is generally perceived negatively by the common population including medical students either due to their religious beliefs or due to their pre-conceived fear. Considering the preconceptions, this study is aimed to assess the attitude, perception and knowledge among the para-clinical medical students. Materials and methods: A cross sectional survey was conducted on 200 paraclinical medical students of Chattagram Maa-O-Shishu Hospital Medical College. A pretested questionnaire was used and data analyzed by SPSS22. Results: Among 200 para-clinical medical students, all attended MLPME but 96% not performed. 49% students first knew about this from TV news and from movies. 62.5% didn’t think doing MLPME was disrespectful to the body. 95.5% agreed that MLPME was necessary in medical education. 77.5% agreed that medical students should perform MLPME. 75.5% of participants felt that the MLPME they witnessed were not enough. 40.5% students were not confident on independently performing the MLPME after completion of their graduation but 39.5% were not sure. 90.5% thought MLPME necessary for all unnatural deaths. In MLPME, 94.5% knew that both external and internal examinations were done. 96.5% knew preserving viscera was necessary during MLPME on suspected case of poisoning. 77.5% thought that saturated salt solution used as preservative. Conclusion: Overall data analysis indicated that para-clinical medical students had reasonable knowledge and positive attitude on MLPME but they felt their exposure on MLPME insufficient.Chatt Maa Shi Hosp Med Coll J; Vol.23 (1); January 2024; Page 24-28